C is your answer i hope u got it right
the equation to this graph is y = 2x -2
Answer:
![New = -92\frac{1}{8}](https://tex.z-dn.net/?f=New%20%3D%20-92%5Cfrac%7B1%7D%7B8%7D)
Step-by-step explanation:
Given:
--- Position
--- Change
Required
Find the new position
The new position is calculated as:
![New = x + \triangle x](https://tex.z-dn.net/?f=New%20%3D%20x%20%2B%20%5Ctriangle%20x)
![New = -75\frac{3}{4} - 16\frac{3}{8}](https://tex.z-dn.net/?f=New%20%3D%20-75%5Cfrac%7B3%7D%7B4%7D%20-%2016%5Cfrac%7B3%7D%7B8%7D)
![New = -75.75 - 16.375](https://tex.z-dn.net/?f=New%20%3D%20-75.75%20-%2016.375)
![New = -92.125](https://tex.z-dn.net/?f=New%20%3D%20-92.125)
![New = -92\frac{125}{1000}](https://tex.z-dn.net/?f=New%20%3D%20-92%5Cfrac%7B125%7D%7B1000%7D)
![New = -92\frac{1}{8}](https://tex.z-dn.net/?f=New%20%3D%20-92%5Cfrac%7B1%7D%7B8%7D)
You said you’d give 30 points but i only see 15 there ☹️
Answer:
4
Step-by-step explanation:
<h3><u>some relevant limit laws</u></h3>
lim C = C where c is a constant.
lim( f(x) + g(x)) =lim f(x) + lim g(x)
lim( f(x)g(x)) =lim f(x) * lim g(x)
lim( cg(x)) =clim g(x)
lim( f(x)/g(x)) =lim f(x) / lim g(x) if lim g(x) is not equal to zero.
lim( f(x))^2 = (lim f(x) )^2
lim square root( f(x)) = square root(lim f(x) )
![\lim_{n \to 3} g(x) = 9\\\\\lim_{n \to 3} f(x) = 6\\\\ \lim_{n \to 3} \sqrt[3]{f(x)g(x) + 10} \\\\ = \lim_{n \to 3} \sqrt[3]{f(x)g(x) + 10}\\\\= \sqrt[3]{lim_{n \to 3}f(x) \times lim_{n \to 3}g(x) + 10}\\\\= \sqrt[3]{6 \times 9 + 10}\\\\= \sqrt[3]{64}](https://tex.z-dn.net/?f=%5Clim_%7Bn%20%5Cto%203%7D%20g%28x%29%20%20%3D%209%5C%5C%5C%5C%5Clim_%7Bn%20%5Cto%203%7D%20f%28x%29%20%20%3D%206%5C%5C%5C%5C%20%5Clim_%7Bn%20%5Cto%203%7D%20%5Csqrt%5B3%5D%7Bf%28x%29g%28x%29%20%2B%2010%7D%20%5C%5C%5C%5C%20%3D%20%5Clim_%7Bn%20%5Cto%203%7D%20%5Csqrt%5B3%5D%7Bf%28x%29g%28x%29%20%2B%2010%7D%5C%5C%5C%5C%3D%20%5Csqrt%5B3%5D%7Blim_%7Bn%20%5Cto%203%7Df%28x%29%20%5Ctimes%20lim_%7Bn%20%5Cto%203%7Dg%28x%29%20%2B%2010%7D%5C%5C%5C%5C%3D%20%5Csqrt%5B3%5D%7B6%20%5Ctimes%209%20%2B%2010%7D%5C%5C%5C%5C%3D%20%5Csqrt%5B3%5D%7B64%7D)
= 4